Analisis Simultan untuk Menentukan Kadar Asam Askorbat dan Niacinamide dalam Serum Wajah Menggunakan Spektrofotometer UV-Visible dengan Pendekatan Kemometrik - Suri, Faradila Azzahra; Auli, Winni Nur; Nareswari, Tantri Liris (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
Ascorbic acid and niacinamide are active brightening ingredients in facial serum skin care products. These two active substances are used together in one product. This research aims to develop a method for analyzing ascorbic acid and niacinamide simultaneously using a chemometric UV-Vis spectrophotometer. The research was carried out by testing specificity using a UV-visible spectrophotometer, and development was carried out by building a Partial Least Square (PLS) model using 20 training sets, which were cross-validated through leave-one-out cross-validation to obtain 5 test sets. Next, internal and external validation was carried out on model and method validation tests focusing on linearity, precision, limit of detection (LOD), and limit of quantification (LOQ). Tests were carried out at wavelengths of 244 and 262 nm. The model and method validation tests' internal and external validation results meet USP requirements. The method for measuring ascorbic acid and niacinamide levels using a UV-Vis chemical spectrophotometer meets the appropriate method validation parameters. The results of concentration measurements in facial serum on the market showed that the sample contained 18.97% ascorbic acid and 13.74% niacinamide. Based on these results, the analysis method for determining the levels of AA and NAC using a UV-Vis spectrophotometer chemometrically has met the validity requirements according to USP.